Efficacy and immunogenicity of a veterinary vaccine candidate against tick-borne encephalitis in dogs - Salat, Jiri; Hunady, Milan; Svoboda, Pavel; Strelcova, Lucie; Strakova, Petra; Fortova, Andrea; Palus, Martin; Ruzek, Daniel (Vaccine, 2023)
Tick-borne encephalitis (TBE) is a severe neuroinfection of humans. Dogs are also commonly infected with tick-borne encephalitis virus (TBEV). These infections are usually asymptomatic, but sometimes show clinical signs similar to those seen in humans and can be fatal. To date, there is no TBEV vaccine available for use in dogs. To address this need, a TBEV vaccine candidate for dogs based on inactivated whole virus antigen was developed. The safety, immunogenicity, and efficacy of the vaccine candidate were tested in mice as the preclinical model and in dogs as the target organism. The vaccine was well tolerated in both species and elicited the production of specific anti-TBEV antibodies with virus neutralising activity. Vaccination of mice provided complete protection against the development of fatal TBE. Immunisation of dogs prevented the development of viremia after challenge infection. Therefore, the developed vaccine candidate is promising to protect dogs from severe TBEV infections.
Keywords: viry klíšťové encefalitidy; Tick-borne encephalitis; psi; Dogs; Encephalitis, Tick-Borne; Vaccination; Mice; vakcinace; Antibodies, Viral; Encephalitis Viruses, Tick-Borne; klíšťová encefalitida; Viral Vaccines; virové vakcíny; Immunization; zvířata; Humans; Vaccine; protilátky virové; myši; imunizace; lidé; Animals